Retroviral insertional mutagenesis implicates E3 ubiquitin ligase RNF168 in the control of cell proliferation and survival. Issue 4 (14th August 2017) - Kizilors, Aytug; Pickard, Mark R.; Schulte, Cathleen E.; Yacqub-Usman, Kiren; McCarthy, Nicola J.; Gan, Shu-Uin; Darling, David; Gäken, Joop; Williams, Gwyn T.; Farzaneh, Farzin
Abstract : The E3 ubiquitin ligase RNF168 is a ring finger protein that has been previously identified to play an important regulatory role in the repair of double-strand DNA breaks. In the present study, an unbiased forward genetics functional screen in mouse granulocyte/macrophage progenitor cell line FDCP1 has identified E3 ubiquitin ligase RNF168 as a key regulator of cell survival and proliferation. Our data indicate that RNF168 is an important component of the mechanisms controlling cell fate, not only in human and mouse haematopoietic growth factor dependent cells, but also in the human breast epithelial cell line MCF-7. These observations therefore suggest that RNF168 provides a connection to key pathways controlling cell fate, potentially through interaction with PML nuclear bodies and/or epigenetic control of gene expression. Our study is the first to demonstrate a critical role for RNF168 in the mechanisms regulating cell proliferation and survival, in addition to its well-established role in DNA repair.